Ten years in the dump: An updated review of the Miocene primate-bearing localities from Abocador de Can Mata (NE Iberian Peninsula). Issue 102 (January 2017) - Alba, David M.; Casanovas-Vilar, Isaac; Garcés, Miguel; Robles, Josep M.
Abstract: More than ten years of paleontological fieldwork during the enlargement of the Can Mata Landfill (Abocador de Can Mata [ACM]), in els Hostalets de Pierola (Vallès-Penedès Basin, NE Iberian Peninsula) led to the recovery of >60, 000 Miocene vertebrate remains. The huge sampling effort (due to continuous surveillance of heavy machinery digging activity, coupled with manual excavation and screen-washing of sediments) enabled generally rare faunal elements such as pliopithecoid and hominoid primates to be found. Thanks to detailed litho-, bio- and magnetostratigraphic controls, accurate dating is possible for all the recovered primate remains from 19 of the 235 localities defined along the 234 m-thick composite stratigraphic sequence of the ACM. Here we report updated estimated (interpolated) ages for these paleontological localities and review the timing of the primate succession in this area. Our results indicate that the whole ACM sequence is late Aragonian in age (MN6 and MN7+8) and includes seven magnetozones that are correlated to subchrons C5Ar.1r to C5r.2r (ca. 12.6 to 11.4 Ma). Great apes (dryopithecines) are first recorded at 12.4–12.3 Ma, but most of the finds ( Anoiapithecus, Pierolapithecus and Dryopithecus ) cluster between 12.0 and 11.9 Ma, followed by some indeterminate dryopithecine remains between 11.7 and 11.6 Ma. Pliopithecoids first appear at 12.1 Ma, being subsequently represented by Pliopithecus between 11.9 and 11.7 Ma. The small-bodied hominoid Pliobates is the youngest ACM primate, with an estimated age of 11.6 Ma. Although these primates probably overlapped in time, their co-occurrence is recorded only twice, at 11.9 Ma (a dryopithecine with Pliopithecus ) and at 11.6 Ma (a dryopithecine with Pliobates ). The rare co-occurrence between great apes and small-bodied catarrhines might be attributable to sampling biases and/or to presumed diverging ecological preferences of these groups. In the future, more detailed analyses of the fauna recovered from the long and densely-sampled ACM sequence will hopefully throw new light on this long-standing, unresolved question.